2008
DOI: 10.1007/s00221-008-1560-0
|View full text |Cite
|
Sign up to set email alerts
|

Position sense asymmetry

Abstract: Asymmetries in upper limb position sense have been explained in the context of a left limb advantage derived from differences in hemispheric specialization in the processing of kinesthetic information. However, it is not clearly understood how the comparison of perceptual information associated with passive limb displacement and the corresponding matching movement resulting from the execution of a motor command contributes to these differences. In the present study, upper limb position sense was investigated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 48 publications
7
52
4
1
Order By: Relevance
“…Position sense asymmetry has been observed in natural [5] and altered [6] conditions. A model-based demonstration including the properties of feedback systems showed that the intrinsic asymmetry in position sense revealed by contralateral matching paradigms resulted from a difference in the gain of each respective sensorimotor system [5].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Position sense asymmetry has been observed in natural [5] and altered [6] conditions. A model-based demonstration including the properties of feedback systems showed that the intrinsic asymmetry in position sense revealed by contralateral matching paradigms resulted from a difference in the gain of each respective sensorimotor system [5].…”
Section: Introductionmentioning
confidence: 98%
“…A model-based demonstration including the properties of feedback systems showed that the intrinsic asymmetry in position sense revealed by contralateral matching paradigms resulted from a difference in the gain of each respective sensorimotor system [5]. In D. E. Adamo is with the department of Health Care Sciences, Wayne State University unperturbed conditions and for right-handed individuals, the right hand overshoots the left hand reference position and the left hand undershoots the right hand reference position.…”
Section: Introductionmentioning
confidence: 98%
“…Both hemispheres can do both predictive and impedance control, but, as a recent model suggests [19] they employ these different control schemes differently during movements. In this context, the slight decrease in constant parallel error found also in the left hand during bimanual mode could be related to increased effort for the right hand to hit the target accurately, and resulting changes in signal gain perception in the kinesthetically controlled left hand [11]. Overall, coordination mode (isodirectional vs. anisodirectional) did not seem to have a specific effect in the sense that one or the other mode improved or degraded either trajectory control or endpoint control.…”
Section: Discussionmentioning
confidence: 94%
“…More recent studies have shown that processing of proprioceptive information seems to be lateralized. For example, dynamic [9], or static position matching tasks [10,11] found the nondominant left limb to be more accurate than the right limb; this was interpreted as left limb/right hemisphere advantage in detecting and processing proprioceptive information. Other experiments, using visuomotor paradigms, also showed that end position accuracy in planar arm movements was higher for the left hand/right hemisphere system http://dx.doi.org/10.1016/j.neulet.2014.…”
Section: Introductionmentioning
confidence: 97%
“…Nonetheless, even in these cases the comparison and interpretation of the data obtained are complicated by the above-mentioned circumstance (the variability of experimental paradigms). For instance, positioning errors in reproduction of the passive movements of a limb link [10] or even errors of reproduction of targeted positioning in the course of movements of the contralateral limb [11,12] were studied in a few works.…”
Section: Introductionmentioning
confidence: 99%